Symbol-error performance and bit-error performance for 2-dimensional signals - Ilakkiyaa D/O Gunasekaran (Nanyang Technological University, 2024)
Due to the technological progress in today’s society, communication systems have become essential and unavoidable. The efficiency of the communication greatly relies on the choice of transmission modulation schemes in addition to the characteristics of channels. This project aims to compute the Symbol Error Rate (SER) and Bit Error Rate (BER). Moreover, this research also examines how various modulation schemes cope with various channel conditions to maximize the performance of digital communication systems.